2008
DOI: 10.1017/s0029665108008069
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and food pattern of Saharawi refugee children in Tindouf (Algeria)

Abstract: The Saharawi refugee camps, including Dakhla, Smara, Al-'Uyun and Awsard, are located in the harsh desert 30 km from Tindouf, the most westerly town in Algeria. They have been the home of 150 000 and 200 000 refugees, including approximately half the indigenous population of Western Sahara, since 1976. International aid groups provide water to the camps, as well as food, medicine and other basic supplies. The aim of the present study was to evaluate the anthropometric measurements, dietary intake and food patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to the HAZ, a high presence of low stature was determined (six children in total), a fact that could be explained considering that the sample studied, whose mean age was 11.1 years, had been lacking adequate nutrition for many years, thus presenting a chronic malnutrition that at the same time increases the probabilities of infections by parasites, in particular, which hinders the progression towards normal growth values. It should be noted that the results of this study are similar to those observed in previous studies of this population that showed that chronic malnutrition is frequent (percentages between 20% and 33%) [2,[4][5][6].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…According to the HAZ, a high presence of low stature was determined (six children in total), a fact that could be explained considering that the sample studied, whose mean age was 11.1 years, had been lacking adequate nutrition for many years, thus presenting a chronic malnutrition that at the same time increases the probabilities of infections by parasites, in particular, which hinders the progression towards normal growth values. It should be noted that the results of this study are similar to those observed in previous studies of this population that showed that chronic malnutrition is frequent (percentages between 20% and 33%) [2,[4][5][6].…”
Section: Discussionsupporting
confidence: 90%
“…Even at these ages, reinfections are usually more frequent than in adulthood, where parasitic infections are usually chronic [32,38]. The results of the coproparasitological analysis stand out from those obtained in other studies carried out in the same area or with children sheltered in different places in Spain [4][5][6][7][10][11][12][13]. In this study, higher prevalence of parasites is observed in general, although it should be noted that the most prevalent parasitic species are the same in practically all studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations